Bioavailability of endotracheal epinephrine in an ovine model of neonatal resuscitation. (March 2019) - Nair, Jayasree; Vali, Payam; Gugino, Sylvia F.; Koenigsknecht, Carmon; Helman, Justin; Nielsen, Lori C.; Chandrasekharan, Praveen; Rawat, Munmun; Berkelhamer, Sara; Mathew, Bobby; Lakshminrusimha, Satyan
Abstract: Background: Distressed infants in the delivery room and those that have completed postnatal transition are both resuscitated according to established neonatal resuscitation guidelines, often with endotracheal (ET) epinephrine at the same dose. We hypothesized that ET epinephrine would have higher bioavailability in a post-transitional compared to transitioning newborn model due to absence of fetal lung liquid and intra-cardiac shunts. Methods: 15 term fetal (transitioning newborn) and 6 postnatal lambs were asphyxiated by umbilical cord and ET tube occlusion respectively. Lambs were resuscitated after 5 min of asystole. ET epinephrine (0.1 mg/kg) was administered after 1 min of positive pressure ventilation (PPV) and chest compressions, and repeated 3 min later, followed by intravenous (IV) epinephrine (0.03 mg/kg) every 3 min until return of spontaneous circulation (ROSC). Serial plasma epinephrine concentrations were measured. Results: Peak plasma epinephrine concentrations were lower in transitioning newborns as compared to postnatal lambs: after a single ET dose (145.36 ± 135.5 ng/ml vs 553.54 ± 215 ng/ml, p < 0.01) and after two ET doses (443 ± 192.49 ng/ml vs 1406 ± 420.8 ng/ml, p < 0.01). The rates of ROSC with a single ET dose were similar in both groups (40% vs 50% in newborn and postnatal respectively, p > 0.99). There was a higher incidence of post-ROSC tachycardia and increased carotid blood flow in the postnatal group. Conclusions: In the postnatal period, ET epinephrine at currently recommended doses resulted in higher peak epinephrine concentrations, post-ROSC tachycardia and cerebral reperfusion without significant differences in incidence of ROSC. Further studies evaluating the optimal dose of ET epinephrine during the postnatal period are warranted. Highlights: Higher peak plasma epinephrine concentrations are noted with endotracheal dosing in post transitional lambs. Post resuscitation tachycardia and increased carotid blood flow is observed in postnatal lambs after endotracheal epinephrine. Higher ranges of the recommended dose of endotracheal Epinephrine (0.05-0.1 mg/kg) should be used with caution postnatally. Further studies are needed to assist in tailoring of ETT epinephrine use and dosing to postnatal age and cause of arrest.